Find the minimum value of x 2 − 2 x y + 2 y 2 + 2 x − 6 y , where x and y are real.
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
f ( x , y ) = x 2 − 2 x y + 2 y 2 + 2 x − 6 y
The minimum values of x and y will satisfy f x = 0 and f y = 0 , or d x d f = 0 and d y d f = 0 .
d x d f = 2 x − 2 y + 2 = 0
→ 2 y = 2 x + 2
→ y = x + 1
Simplifying the above equation gives that y = x + 1 , so we can now plug that value into y in the second equation to solve for x .
d y d f = − 2 x + 4 y − 6 = 0
→ − 2 x + 4 ( x + 1 ) − 6 = 0
→ 4 x + 4 − 2 x − 6 = 0
→ 2 x = 2
→ x = 1
So now that we know that x = 1 , we can plug that into y = x + 1 to solve for y .
This gives that y = 2 and x = 1 as the minimum values of x and y .
Finally, to solve for the minimum value of f ( x , y ) , we just need to plug the values above into the function.
f ( x , y ) = ( 1 ) 2 − 2 ( 1 ) ( 2 ) + 2 ( 2 ) 2 + 2 ( 1 ) − 6 ( 2 )
→ 1 − 4 + 8 + 2 − 1 2 = − 5
So, the answer is -5
Problem Loading...
Note Loading...
Set Loading...
f ( x , y ) = x 2 − 2 x y + 2 y 2 + 2 x − 6 y = ( x − y + 1 ) 2 + y 2 − 4 y − 1 = ( ( x − 1 ) − ( y − 2 ) ) 2 + ( y − 2 ) 2 − 5 Note that ( x − y + 1 ) 2 = x 2 + y 2 + 1 + 2 ( − x y − y + x ) and ( y − 2 ) 2 = y 2 − 4 y + 4
Note that g ( x , y ) = ( ( x − 1 ) − ( y − 2 ) ) 2 + ( y − 2 ) 2 ≥ 0 . Therefore, f ( x , y ) is minimum when g ( x , y ) is minimum or g ( x , y ) = 0 , ⟹ min ( f ( x , y ) = f ( 1 , 2 ) = 0 − 5 = − 5 .